Small Dual Polarized UWB Antenna and Its Array Analysis for 5G/6G Applications - Dastkhosh, Amir Reza; Mehbodniya, Abolfazl; Webber, Julian; Naseh, Mehdi; Dadras Jedi, M.; Lin, Fujiang (Ital Publication, 2025)
In this work, a novel low-profile tunable ultra-wideband (UWB) K/Ka-band (14–40 GHz) dual circularly polarized magneto-electric antenna element has been designed, analyzed, and validated through circuit modeling, simulations, fabrication, and experimental testing for application in 5G/6G phased-array antennas. The antenna has compact dimensions of 0.5λ₀× 0.5λ₀ × 0.06λ₀/0.09λ₀, which can be further reduced to 0.25λ₀× 0.25λ₀ × 0.05λ₀ when metal–insulator–metal (MIM) and/or gap capacitors are employed. The proposed antenna exhibits a high gain of 9 dB, a wide scanning angle of ±75°, and an efficiency exceeding 85% across the entire operating frequency band. In addition, it demonstrates high isolation between ports and between co-polarized and cross-polarized radiation patterns, reaching 25 dB. The resonant frequency of the antenna is tunable, with a variation of up to 97% over the K/Ka-band frequency range. This tuning capability is achieved using MIM capacitors connected to the vias of the circular patch and/or gap capacitors, which collectively function as split-ring resonators (SRRs). Fabrication and experimental testing of the antenna confirm good agreement with the simulated results. The antenna is easily fabricated using glass substrates and standard epoxy/glass processes with only two layers, making it highly suitable for antenna-in-package applications based on glass technology. Since the antenna element is specifically designed for phased-array applications, array configurations were also investigated. Analysis of 512-element arrays shows that the Sunflower layout provides enhanced gain and overall performance while utilizing more than 50% fewer antenna elements compared to a conventional rectangular array.